ECONOMICS STORY BOOK UNTUK MENANAMKAN RASIONALITAS BEREKONOMI SEJAK DINI - Aditya Dewantari; Eka Prayudhista (Universitas PGRI Semarang, 2018)
The role of schools in providing economic education from an early age should be maximized through non-formal or informal education as new economic education begins to be taught in the earliest schools at Junior High School level. In this research will be developed a story book in which contains a message on how to conduct economic activities in a rational manner so that children understand and can apply it in everyday economic activities.This research is a development research using Design Based Research development model. Based on the results of this study it is found that economic storybooks that have been developed are feasible to be used with the percentage of assessment from material experts of 86.72% (very feasible), and the percentage of assessment from media experts of 90.20% (very feasible). In addition, this story book is also effective to provide knowledge about the economic rationality that can be seen from the field trial results with a percentage of success of 80% (very good).